A fresh look at inter-service intervals in UK dairy herds - Remnant, J.G.; Huxley, J.N.; Hudson, C.D. (British Cattle Veterinary Association, 2014)
Good heat detection is essential for good reproductive performance in the modern dairy herd using artificial insemination. Veterinary surgeons and farmers use a variety of tools to monitor heat detection including the analysis of inter-service intervals (ISIs). The aim of this study was to explore the distribution of inter-service intervals in a large sample of UK dairy herds and establish targets for use by practitioners when interpreting ISIs. In this study service records from 167 dairy herds from across the UK were used to generate ISI profiles for each calendar year of each herd. Intervals between serves were categorised as short irregular (2-17 days), short regular (18-24 days), long irregular (25-35 days), long regular (36-48 days) or extended (>48 days). Herd years were ranked by oestrus detection efficiency, the mean of the top quartile of herd-years had 6%, 40%, 16%, 19% and 19% of intervals in each interval category respectively. There was no correlation between the percentage of serves falling in the short regular and short irregular category for a given herd-year (Spearman rho magnitude <0.01, p=0.84), suggesting little direct correlation between the sensitivity and specificity of a herd’s heat detection. The results show a substantial difference to accepted targets and will be of use when interpreting herd data and target setting for UK dairy herds.